Amiodarone with or without N-Acetylcysteine for the Prevention of Atrial Fibrillation after Thoracic Surgery: A Double-blind, Randomized Trial. (9th March 2022) - Amar, David; Zhang, Hao; Chung, Mina K.; Tan, Kay See; Desiderio, Dawn; Park, Bernard J.; Pedoto, Alessia; Roistacher, Nancy; Isbell, James M.; Molena, Daniela; Milne, Ginger L.; Meyers, Bryan F.; et al.
Abstract : Background: Postoperative atrial fibrillation may identify patients at risk of subsequent atrial fibrillation, with its greater risk of stroke. This study hypothesized that N -acetylcysteine mitigates inflammation and oxidative stress to reduce the incidence of postoperative atrial fibrillation. Methods: In this double-blind, placebo-controlled trial, patients at high risk of postoperative atrial fibrillation scheduled to undergo major thoracic surgery were randomized to N -acetylcysteine plus amiodarone or placebo plus amiodarone. On arrival to the postanesthesia care unit, N -acetylcysteine or placebo intravenous bolus (50 mg/kg) and then continuous infusion (100 mg/kg over the course of 48 h) was administered plus intravenous amiodarone (bolus of 150 mg and then continuous infusion of 2 g over the course of 48 h). The primary outcome was sustained atrial fibrillation longer than 30 s by telemetry (first 72 h) or symptoms requiring intervention and confirmed by electrocardiography within 7 days of surgery. Systemic markers of inflammation (interleukin-6, interleukin-8, tumor necrosis factor α, C-reactive protein) and oxidative stress (F2 -isoprostane prostaglandin F2α ; isofuran) were assessed immediately after surgery and on postoperative day 2. Patients were telephoned monthly to assess the occurrence of atrial fibrillation in the first year. Results: Among 154 patients included, postoperative atrial fibrillation occurred in 15 of 78 who received N -acetylcysteine (19%) and 13 of 76 who received placebo (17%; odds ratio, 1.24; 95.1% CI, 0.53 to 2.88; P = 0.615). The trial was stopped at the interim analysis because of futility. Of the 28 patients with postoperative atrial fibrillation, 3 (11%) were discharged in atrial fibrillation. Regardless of treatment at 1 yr, 7 of 28 patients with postoperative atrial fibrillation (25%) had recurrent episodes of atrial fibrillation. Inflammatory and oxidative stress markers were similar between groups. Conclusions: Dual therapy comprising N -acetylcysteine plus amiodarone did not reduce the incidence of postoperative atrial fibrillation or markers of inflammation and oxidative stress early after major thoracic surgery, compared with amiodarone alone. Recurrent atrial fibrillation episodes are common among patients with postoperative atrial fibrillation within 1 yr of major thoracic surgery. Abstract : This double-blinded randomized trial of noncardiac thoracic surgery patients was done to test the hypothesis that the addition of N -acetylcysteine to concurrent amiodarone administration would reduce the incidence of postoperative atrial fibrillation when compared with placebo being concurrently administered with amiodarone. The study was halted midway for futility, as there was no difference in postoperative atrial fibrillation in the patients who received N -acetylcysteine plus amiodarone versus the patients who received placebo plus amiodarone.